Dishevelled 2 regulates cancer cell proliferation and T cell mediated immunity in HER2-positive breast cancer - Fahmida Rasha; Geetha Priya Boligala; Mingxiao V. Yang; Dalia Martinez-Marin; Isabel Castro-Piedras; Kathryn Furr; Annie Snitman; Sonia Y. Khan; Luis Brandi; Maribel Castro; Hafiz Khan; Nusrat Jahan; et al. (BMC Cancer, 2023)
Abstract Background Dishevelled paralogs (DVL1, 2, 3) are key mediators of Wnt pathway playing a role in constitutive oncogenic signaling influencing the tumor microenvironment. While previous studies showed correlation of β-catenin with T cell gene expression, little is known about the role of DVL2 in modulating tumor immunity. This study aimed to uncover the novel interaction between DVL2 and HER2-positive (HER2+) breast cancer (BC) in regulating tumor immunity and disease progression. Methods DVL2 loss of function studies were performed with or without a clinically approved HER2 inhibitor, Neratinib in two different HER2+ BC cell lines. We analyzed RNA (RT-qPCR) and protein (western blot) expression of classic Wnt markers and performed cell proliferation and cell cycle analyses by live cell imaging and flow cytometry, respectively. A pilot study in 24 HER2+ BC patients was performed to dissect the role of DVL2 in tumor immunity. Retrospective chart review on patient records and banked tissue histology were performed. Data were analyzed in SPSS (version 25) and GraphPad Prism (version 7) at a significance p < 0.05. Results DVL2 regulates the transcription of immune modulatory genes involved in antigen presentation and T cell maintenance. DVL2 loss of function down regulated mRNA expression of Wnt target genes involved in cell proliferation, migration, invasion in HER2+ BC cell lines (±Neratinib). Similarly, live cell proliferation and cell cycle analyses reveal that DVL2 knockdown (±Neratinib) resulted in reduced proliferation, higher growth arrest (G1), limited mitosis (G2/M) compared to non-targeted control in one of the two cell lines used. Analyses on patient tissues who received neoadjuvant chemotherapy (n = 14) further demonstrate that higher DVL2 expression at baseline biopsy pose a significant negative correlation with % CD8α levels (r = − 0.67, p < 0.05) while have a positive correlation with NLR (r = 0.58, p < 0.05), where high NLR denotes worse cancer prognosis. These results from our pilot study reveal interesting roles of DVL2 proteins in regulating tumor immune microenvironment and clinical predictors of survival in HER2+ BC. Conclusion Our study demonstrates potential immune regulatory role of DVL2 proteins in HER2+ BC. More in-depth mechanistic studies of DVL paralogs and their influence on anti-tumor immunity may provide insight into DVLs as potential therapeutic targets benefiting BC patients.